Endogenous network effects - Ralf Dewenter; Franziska Löw (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2022)
In contrast to traditional business models, two-sided platforms internalize indirect network effects that exist between different groups of platform participants. The strength of the network effects has a decisive influence on the success of the platform and its market position. Markets with particularly strong network effects are also often characterized by a high degree of concentration. However, the strength of the network effects is not exogenously given but can be influenced by targeted investment. This paper analyses how platforms can affect network effects by investing in appropriate infrastructure, data, or artificial intelligence. We derive optimal quantities, prices, profits, and investments depending on different types of investments.
Keywords: D21; D42; L10; 330; two-sided markets; indirect network effects; endogenous network effects; optimal investment strategy